IDENTIFYING PROPOLIS COMPOUNDS POTENTIAL TO BE COVID-19 THERAPIES BY TARGETING SARS-COV-2 MAIN PROTEASE - DEWI, LIA KUSUMA; SAHLAN, MUHAMAD; PRATAMI, DIAH KARTIKA; AGUS, ALI; AGUSSALIM; SABIR, ARDO (International Journal of Applied Pharmaceutics, 2021)
Objective: The study aims to perform molecular docking to examine the interaction between propolis compound and SARS-CoV-2 main protease. Methods: The protein target of this research was the crystal structure of SARS-CoV-2 main protease in complex with an inhibitor N3 (PDB ID: 6LU7). The ligand of this research was the bioactive compounds from Propolis of Tetragonula aff. biroi. Results: The results showed that propolis compound which has the potential to inhibit SARS-CoV-2 protease activity was Sulabiroins A (binding affinity-8.1 kcal/mol), following by (2S)-5,7-dihydroxy-4'-methoxy-8-prenylflavanone acid and broussoflavonol F (binding affinity-7.9 kcal/mol) with binding similarity more than 50% compared to N3-main protease interaction. Conclusion: Molecular docking showed propolis compounds of Tetragonula aff. biroi potential to inhibit SARS-CoV-2 main protease activity. The highest binding affinity presented by Sulabiroins A, following by (2S)-5,7-dihydroxy-4'-methoxy-8-prenylflavanone acid and broussoflavonol F, with values of-8.1 kcal/mol,-7.9 kcal/mol, and-7.9 kcal/mol, respectively, with binding similarity more than 50% compared to N3 and SARS-CoV-2 main protease interaction.